Laparoscopic electrochemotherapy for the treatment of hepatocellular carcinoma: Technological advancement - Trotovsek, Blaz; Hadzialjevic, Benjamin; Cemazar, Maja; Sersa, Gregor; Djokic, Mihajlo (Frontiers in Oncology, 2022)
Electrochemotherapy is an effective treatment modality for hepatocellular carcinoma (HCC). Electrochemotherapy for HCC was initially used in the setting of open surgery. Recently, with the development of newer electrodes, percutaneous approaches have also been performed. However, laparoscopic application of electrochemotherapy for HCC has not yet been described. Two patients with unresectable HCC were enrolled in the study. The first patient was not suitable for the percutaneous approach because the tumor was located close to the gallbladder. He also had symptomatic gallstones. The second patient had HCC in close proximity to the stomach and was therefore not suitable for percutaneous access or any other ablative technique. Thus, the laparoscopic approach was chosen, using newly developed Stinger electrodes for the application of electric pulses. After intravenous administration of bleomycin, several sets of electric pulses were delivered to the whole tumor mass in both patients. Ultrasonographically, the coverage of the whole tumor was verified, as described previously. Cholecystectomy was also performed in the first patient. Follow-up abdominal computed tomography showed a complete response of the treated lesions in both patients. Minimally invasive laparoscopic electrochemotherapy is safe, feasible and effective method for the treatment of HCC. It could be used in patients in whom the percutaneous approach is unsafe (proximity to other organs) and in patients with concomitant symptomatic gallstones in whom cholecystectomy is already indicated. This technological approach thus allows broader and minimally invasive clinical applicability of electrochemotherapy.